Athletic Identity of Students Actively Involved in Sports and Its Relationship with Induced Stress - Indriuniene, Vinga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Theexpression of the athletic identity in academic environments may become a stress-reducing and a stress-enhancing factor depending on the conditions of the environment when expressing one’s athletic identity (Chen et al., 2010).Methods. 214 students (105 females and 109 males) took part in the research. All of them were first year students of the first level of studies (i.e. BA studies) at Lithuanian Sports University. All the students were actively practicing sports. Their age ranged from 18 to 25 with the age average of 19.24 (0.76). Thestudymadeuseofquestionnaires: ReederStressAssessmentScale and Athletic Identity Questionnaire (AIQ).Conclusions. The stress levels experienced by students actively practicing sports and possessing a more prominent athletic identity yet not going for results in sports are lower than those experienced by students with a less prominent athletic identity.